Analysis of Clean Water Needs, Quality and Availability Projections in 2032 (Case Study: SMK Negeri 2 Manokwari) - Johra, Johra; Ritnawati, Ritnawati; Marzuki, Ismail (Universitas Ibn Khaldun Bogor, 2023)
SMK Negeri 2 Manokwari West Papua Province is one of the vocational high schools that foster 12 competencies in the field of Technology and Engineering with 1,567 people active in 2022. To support daily activities at school, the availability of clean water in the school environment is necessary for washing hands, defecating, and urinating. The availability of clean water is at least balanced with the need for clean water, this is intended to ensure that school needs are fulfilled. This study aims to analyze the need for clean water and clean water quality by quality standards. Clean water needs are analyzed using a mathematical approach based on clean water planning criteria, while the clean water quality analysis is carried out by testing clean water samples through the Manokwari City BPOM laboratory. The results showed that the need for clean water in schools was 17,280 liters/day. Water distribution to bathrooms/toilets, sinks, and public face, uses a piping network sourced from 2 reservoirs with a capacity of 40,400 liters. The source of raw water used is groundwater and pumping systems. For the analysis of clean water quality, the data shows that the temperature parameter = 0.05 oC, pH = 7.88, TDS = 0.3060 mg/L, and coliform number = 27.09 x 10^1 CFU/100 mL, so that the water quality microbiologically does not meet the requirements for sanitary hygiene. While the results of the study showed that the need for clean water in SMK Negeri 2 Manokwari until 2032 reached 33,276 L/day (47.21%). The results of this study are expected to be useful for the development of science for academics in universities, government and society. E, especially for students at SMK Negeri 2 Manokwari, hopefully, it will be interesting reading material in the school library.